Morfologi Jenis - Jenis Tumbuhan Pada Lahan Reklamasi Tambang Batubara Bukit Asam Tanjung Enim - Dana Mega Lestari; Syamsul Rizal; Inka Dahlianah (Indobiosains, 2022)
ABSTRACTThis study on the morphology of plant species in the Bukit Asam Tanjung Enim Coal Mine Reclamation Land, has been carried out from May 2021 to June 2021. The purpose of this study was to the determine the morphology and types of plants on the coal mine reclamation land inTanjung Enim. This study uses a deskriptive survey method. Sampling using purposive sampling with exploring techniques. The results obtained are 12 plant species, namely: Kayu putih (Melaleca leucadendra (L)),Akasia ( Acacia mangium ), Lamtoro ( Leucaena leucocephala ), Mahoni ( Swietenia macrophilla King ), Tanjung ( Mimusops elengi Linn ), Waru ( Hibiscus tiliaceus ),Seru ( Schima wallichii ), Kelapa sawit ( Elaeis guineensis ), Jati ( Tectona grandis ), Trembesi ( Samanea saman ), Angsana ( Pterocarpus indicus Willd ), Sengon ( Paracerienthes falcataria (L)).Morphological observations on the root (Radix), stem (Caulis), leaf (Folium), flower (Flos), fruit (Fructus). System that has been obtained is a tap root (Radix primaria) and fibers root (Radix adventica). Types of woody trunk (Lignosus), single leaf types (Folium simplex) and compound (Folium compositum), single flowers and compound flowers,and there are 4 types of fruit, namely box fruit, buni fruit, stone fruit and pod. Keywords: Morphology, Land Use